S‐Adenosyl‐L‐Homocysteine Hydrolase Immobilized on Citric Acid‐capped Gallium Oxyhydroxide on SWCNTs Modified Electrode for AdoHcy Impedimetric Sensing. Issue 1 (7th October 2021) - Knežević, Sara; Ognjanović, Miloš; Gavrović Jankulović, Marija; Đurašinović, Tatjana; Antić, Bratislav; Djurić, Sanja Vranješ; Stanković, Dalibor M.
Abstract: S‐Adenosyl‐L‐Homocysteine (AdoHcy) is a crucial pathological factor in homocysteine‐associated disorders. We developed an impedimetric approach for single drop S‐Adenosyl‐L‐Homocysteine detection, based on S‐Adenosyl‐L‐Homocysteine hydrolase (SAH), produced in the prokaryotic expression system (E. coli) by recombinant DNA technology, immobilized on citrate acid‐coated gallium oxyhydroxide dispersed over single‐walled carbon nanotubes (CA/GaO(OH)@SWCNT). The proposed biosensor offers detection of AdoHcy, with a limit of detection (LOD) of 0.17 μM. with operating linear range from 1 to 44 μM. The remarkable stability of gallium oxyhydroxide crystal was further improved by citric acid coating and its optical, electrical and physical anisotropy was skipped using SWCNTs. Abstract :